DETERMINATION OF ANTIOXIDANT ACTIVITY AND VITAMIN C OF SOME WILD FRUITS OF MANIPUR - SUSHMA KHOMDRAM; G. A. SHANTIBALA DEVI (The Bioscan, 2010)
Fruits are excellent sources of natural antioxidant and vitamins, especially ascorbic acid or vitamin C and fruits having very rich vitamin C are known to have very strong antioxidant properties. Vitamin C was estimated by using 2, 6-dichlorophenol indophenol reagent and antioxidant activity by DPPH (2, 2-diphenyl-1-picrylhydrazyl). The wild fruits of Manipur on analysis reveal that Emblica officinalist (amla) has very high amount of vitamin C (379.7 mg/100g) and simultaneously its antioxidant activity was also maximum (IC50 181μg/mL) from among the selected samples. The present work is a brief screening of these wild fruits to explore their significant values as nutrition for mankind.